Tailoring Acculturation Scale for Malaysian Students in Japan Universities - Ina Suryani, Ab Rahim; Kaur, Kuldip; Intan, Maslina (INTI International University, 2007)
Adjustment to a new culture is crucial psychological and behavioural process among international students. Adaptation supports the performance and functioning of these students. Failure to adapt to the changes in the new environment would tax on the psychological wellbeing, exhaust the students and strain the academic performance. Acculturation is one the important moderating factor for adaption and studies have shown that it may affect the academic performance amongst the international students. Acculturation can be assessed by measuring the assimilation into the host culture and retention of the origin culture. The western acculturation models have developed to a comprehensive description. From these models, acculturation scales have been created. This paper looks into the relevant construct from the existing acculturation scales such as Indonesian Acculturating Scale (IARS) proposed by Hondojo (2000) and Acculturative scale for Asian (ASA) by Kim (2001). The items derived from these acculturation scales are pooled and then tested on 30 Asian International students in Islamic International University (IIU), Malaysia. Findings show that some of the items for the scale are significant. Further interview brings on a possible extension on the theory of acculturation strategy; which is a possibility of Alternative culture in addition to the two suggested by the western research. It is hoped that this study would support effective counselling by suggesting evidence in avoiding generalization and stereotyping of western cases in the counselling, orientation and intervention programs for Malaysian students in Japan Universities.